Strategic vision for the development of livestock in Brazil (Revista Sistemas de Producción Agroecológicos, 2014)
This text is presented as it was the meat market, the impact on the Brazilian economy and the situation is compared globally. Given the economic importance of livestock productions in the international market whit emphasis on livestock development in Brazil, from public policies related to livestock production and support the meat industry. In conclusion, the future of the meat market and agribusiness in Brazil is promising given the availability of land and water existing in the country, making investment in human capital, technology and infrastructure.
Keywords: Cost of production; meat industry; beef production